Income and Asset Disclosure Systems : Establishing Good Governance through Accountability - Burdescu, Ruxandra (World Bank, Washington, DC, 2012)
Financial declarations or income and asset disclosures (IADs) are quickly becoming an important tool for anticorruption agencies and governments to fight corruption. IAD systems can play two important roles within a broader framework of good governance: prevention and enforcement. In an effort to discover how best to design and implement an IAD system, the analysis conducted suggests that countries ultimately must design a system that best complements the environment in which it will function. However, there are several key principles that policy makers and practitioners need to consider: limit the number of filers to improve the odds of success, set modest and achievable expectations, provide resources commensurate with the mandate, and prioritize verification procedures to align with available resources, and balance privacy concerns with public access to declarations.